(untitled) (Research, Society and Development, 2026)
Regular physical exercise is essential for health promotion; however, low adherence remains a significant challenge. In this context, this study aimed to analyze the motivational factors associated with adherence to physical exercise, as well as their implications for the role of Physical Education professionals. This study is an integrative literature review with a qualitative approach, conducted through searches in PubMed, SciELO, and the Virtual Health Library, including studies published between 2016 and 2026. The results indicate that self-determined motivation, particularly intrinsic motivation, is positively associated with exercise adherence; furthermore, the satisfaction of basic psychological needs, such as autonomy, competence, and relatedness, along with positive affective experiences, social support, and self-efficacy, showed a significant influence on adherence. In addition, interventions based on Self-Determination Theory, combined with the support provided by Physical Education professionals, contribute to greater engagement and persistence. It is therefore concluded that adherence to physical exercise is a multifactorial phenomenon, highlighting the importance of strategies that consider psychological and social aspects to promote long-term adherence and health improvement.